Comparative study of accompaniment programs for undergraduate degree students in Spanish universities - García-Cardo, Susana; Queiruga-Dios, Marián; Queiruga-Dios, Araceli (Frontiers in Psychology, 2023)
Introduction In the last decade, higher education has undergone a transformation in different areas. The most recent and impactful one may have been the need to keep it updated during the COVID-19 pandemic and to be able to teach remotely and affect university life as little as possible. Another significant change is the emergence of personal attention, accompaniment, or mentoring programs, which have become the prevalent leitmotif in many universities. Methods This study compares the different programs at 60 Spanish universities. The relevant information collected during this research is related to the existence of an accompaniment program, and in this program, which plays the role of mentor, or what year is it for. Other information collected from the search is related to the type of mentoring programs, whether they are regulated, have a formal program, or are linked to specific courses. Finally, the assessment procedures are also indicated in case any evaluation is used. After the analysis developed during this research, the mentor-mentee program implemented at the Francisco de Vitoria University is detailed, highlighting differences from other programs, its advantages, and students' benefits. Results The number of accompaniment and mentoring programs offered by Spanish universities continues to rise. In Spanish universities, some accompaniment and mentoring programs offer different and specific mentoring activities designed to enhance and further the kind of education and preparation institutions of higher learning should ideally provide. Accompaniment processes generally have a longer duration in private universities than in public universities, offering a wider range of programs for both current and incoming students and those with specific needs, such as international students. Discussion The authors found that not many studies have highlighted the value of the accompaniment, and even fewer have conducted comparative analyses of the diverse realities across various universities. Mentoring programs will have the potential to be part of a university's strategy to help students succeed when the shortcomings of mentoring programs. This study opens new avenues for research into the ideal profile of mentors to best accompany university students.